Primary surgery for locoregional advanced oropharyngeal cancer: prognostic factors - Gomes, Patrícia S.; Breda, Eduardo; Monteiro, Eurico (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Oropharyngeal squamous cell carcinoma (OPSCC) incidence is rising in developed countries. These malignancies usually present in advanced stages and are associated with poor outcome. This work aims to ascertain the clinical and histopathological prognostic factors of locoregional advanced OPSCC treated with primary surgery in a tertiary oncology centre. Methods: Retrospective chart review of all patients with advanced OPSCC who underwent primary surgery from 2011 to 2016. Overall and disease-free survivals were estimated using Kaplan-Meier method. Clinical and histopathological prognostic factors were determined by univariate (Log Rank tests) and multivariate (Cox models) analyses. Results: 89 patients (89.9% male) with a mean age of 57.6±10.0 years were included in the study. Five-year overall and disease-free survivals were 53.9% and 57.7%, respectively. Pathologic N stage (HR=2.65 95% IC 1.32-5.32, p<0.01), distant metastasis (HR= 3.26 95% IC 1.24-8.62, p=0.01) and postoperative radiotherapy (HR=0.02 95% IC 0.01-0.12, p<0.01) were significantly correlated with overall survival. Pathologic N stage (HR=2.41, 95% IC 1.04-5.63, p=0.04) perineural infiltration (2.45, 95% IC 1.01-5.95 p=0.04), distant metastasis (HR=5.24, 95% IC 2.31-11.89, p<0.01) and postoperative radiotherapy (HR=0.02 95% IC 0.00-0.18, p<0.01), were significantly correlated with locoregional disease-free survival. Conclusions: Knowledge of survival prognostic factors is crucial for selection of the appropriate treatment of oropharyngeal cancer. Pathological nodal stage, postoperative radiotherapy and the occurrence of distant metastasis were the main prognostic factors for overall and disease-free survivals in the present series. These findings may help to provide proper stratification in future randomized trials.